Pengaruh Jenis Limbah Agro Industri Terhadap Keragaan Bibit Sawit Main Nursery pada Ultisol - Dewi Riniarti; Any Kusumastuti; M. Tahir (Politeknik Negeri Lampung., 2013)
This study aims to (1) the effect of type of waste on the performance of oil palm seeds (2) get the best incubation time to obtain good quality compost and its effect on the performance of seeds (3) get a good composition of the media to get the performance of both oil palm seedlings and its influence terhdap Ultisol physical properties, and (4) the effect of interaction between the type of waste, a long incubation, and the composition of the planting medium terhdap the performance of oil palm seedlings and Ultisol physical properties. The experiment was conducted in Palm Nursery Polytechnic Lampung from July 2009 until April 2010., Designed in factorial randomized block design. The treatments consisted of 3 (three) factors. The first factor is the type of waste consisting of sugar cane waste (bagase) and empty fruit bunches (Tankos) palm oil. The second factor is the length of incubation of waste, consisting of 2 (two) and 3 (three) weeks. Factors to 3 (three) is the composition of media, namely: 1 (compost): 4 (ground); 1 (compost): 5 soil, and 1 (sand): 4 (ground) as a control. Each treatment was replicated 3 (three) times, each experimental unit consisted of two seeds. The results showed that the sugar agro waste (bagasse) effect on plant height is better than empty fruit bunches Palm Oil (Tankos); waste Incubation period 3 weeks performed better on the character of dry weight, ratio of crown root and seedling growth rate; Bagas incubated 3 weeks influential The best in plant height; media composition had no effect on the growth characteristics of oil palmseedlings in the main nursery. Keywords: Oil Palm Seedlings, bagase, empty fruit bunches palm oil, incubation periode, and ultisol.